View Single Post
Old 2005-01-17, 06:21   #2
jinydu
 
jinydu's Avatar
 
Dec 2003
Hopefully Near M48

2·3·293 Posts
Default

Hi tinhnho

(t+1)/(t+4)^2 = K1/(t+4) + K2/(t+4)^2

Continue by multiplying both sides by (t+4)^2:

t+1 = K1*(t+4) + K2

t+1 = (K1*t) + (4K1 + K2)

Equating coefficients for t, we have

K1 = 1

Equating constant coefficients, we have:

4K1 + K2 = 1

4 + K2 = 1

K2 = -3

Thus, the partial fraction representation is:

f(t) = 1/(t+4) - 3/(t+4)^2

Mathematica agrees.
jinydu is offline   Reply With Quote